A comparative evaluation of kambin’s triangle approach versus safe triangle approach for lumbar transforaminal epidural injection in patients with lumbar radiculopathy - A prospective, randomized, double blind study - Biswas, Rajasree; Choudhury, Arpita; Bhattacharya, Dipasri; Nandy, Sabyasachi (Asian Journal of Medical Sciences, 2021)
Background: Epidural injection of steroid and local anaesthetic is a common modality for management of radicular pain. Transforaminal approach is preferred for epidural injection in case of radiculopathy. Aims and Objectives: To compare the effect of the Kambin’s triangle and subpedicular approaches of transforaminal epidural injection (TFEI) in patients of lumbar radiculopathy. Materials and Methods: Forty patients with lumbar radicular pain were enrolled and randomly assigned to each group (Group K for Kambin’s triangle approach and Group S for subpedicular approach). All procedures were performed under fluroscopic guidance. The frequency of complications during the procedure and the effect of TFEI at 2 and 4 weeks after the procedure between the two groups were compared. Short-term outcomes were measured using a visual Analog scale (VAS). Multiple logistic regression analyses were performed to evaluate the relationship between possible outcome predictors and the therapeutic effect. Result: VAS was improved 2 weeks after the injection and continued to improve until 4 weeks in both groups. There were no statistical differences in changes of VAS between these two groups. Spinal nerve pricking occurred in one case of the subpedicular and in none of the cases of the Kambin’s triangle approach (p<0.05). Conclusion: Kambin’s triangle approach is as efficacious as the subpedicular approach for short-term effect and offers considerable advantages (i.e., less spinal nerve pricking during procedure). So, Kambin’s triangle approach may be an alternative method for TFEI in cases where needle tip positioning in the anterior epidural space is difficult.